Participation, academic influences and interactions: A comparison of Chinese and U.S. research universities on ResearchGate - Yan, Weiwei; Zhang, Yin (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2021)
ResearchGate (RG) is an academic social networking (ASN) site that is used worldwide for scholarly communication. This study examines RG users from 21 top Chinese research universities and 61 U.S. research universities from three research activity levels to identify the differences in participation, interactions, and academic influences between their affiliated institutions on this ASN platform. The implications on scholarly communication and evaluation using altmetrics across nations are discussed.